Pengaruh Implementasi Kebijakan Efisiensi Anggaran dan Akuntabilitas Pengelolaan APBD Terhadap Kinerja Pegawai Badan Pengelola Keuangan dan Aset Daerah Kabupaten Pesawaran - Ahmad Dirmansyah Perwiranegara; Iskandar Ali Alam (Al-Kharaj: Jurnal Ekonomi, Keuangan & Bisnis Syariah, 2026)
This study aims to analyze and test the influence of budget efficiency policy implementation and APBD management accountability on employee performance at the Regional Financial and Asset Management Agency (BPKAD) of Pesawaran Regency. The focus of this research is crucial following the issuance of Presidential Instruction (Inpres) Number 1 of 2025 concerning Expenditure Efficiency, which resulted in the adjustment of non-monetary incentives for employees. The research method used is quantitative with a causal associative design. The population in this study consisted of 60 employees of BPKAD Pesawaran Regency, where the sampling technique utilized total sampling (census). Data were collected through questionnaires with a Likert scale and analyzed using multiple linear regression via SPSS software. The results showed that simultaneously, budget efficiency and accountability had a significant effect on employee performance with a coefficient of determination (R2) of 66.6%. Partially, APBD management accountability has a positive and significant effect on employee performance (Sig. 0.000). However, the implementation of budget efficiency policy has a positive but not significant effect on employee performance (Sig. 0.083 > 0.05). This indicates that the performance of BPKAD Pesawaran Regency employees is more driven by the demands of system compliance and reporting transparency rather than budget saving policies. Organizational leaders are advised to formulate non-monetary motivation strategies to maintain performance stability amidst strict fiscal efficiency policies